EMPOWERING MSMES IN UTILIZING MARKETPLACE APPLICATIONS IN CEMENGKALANG VILLAGE - Permata, Ellena Dias; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the empowerment efforts of Micro, Small, and Medium Enterprises (MSMEs) through the use of marketplace applications in Cemengkalang Village, addressing the relevance of MSME empowerment in improving the local economy amidst globalization and the development of information technology. Method: The research method used was qualitative, with data collection through in-depth interviews, observation, and documentation. Result: The results showed that MSMEs experienced increased market access and skills through training in the use of marketplace applications such as Shopee, TikTok, and Tokopedia, with sales increases of up to 30–50%, although challenges such as technological limitations and low digital literacy among consumers remain obstacles, indicating the need for more intensive support and training to maximize MSME potential in the digital era. Novelty: The novelty of this study lies in the use of a local, village-based approach that combines empowerment according to Fahrudin—emphasizing individual capacity, community participation, access to resources, and MSME independence—with digital implementation through marketplace applications, while also identifying structural barriers and challenges of digital culture at the community level and highlighting the role of social solidarity among business actors in supporting digital transformation.